Neutrosophic Parameterized Soft Relations and Their Applications - Irfan Deli; Yunus Toktas; Said Broumi (Neutrosophic Sets and Systems, 2014)
The aim of this paper is to introduce the concept of relation on neutrosophic parameterized soft set (NP- soft sets) theory. We have studied some related properties and also put forward some propositions on neutrosophic parameterized soft relation with proofs and examples. Finally the notions of symmetric, transitive, reflexive, and equivalence neutrosophic parameterized soft set relations have been established in our work. Finally a decision making method on NP-soft sets is presented.